Urgensi Pelindungan Satwa Terhadap Masifnya Kegiatan Perburuan Liar di Kawasan Hutan Kalurahan Kepuharjo, Kapanewon Cangkringan, Kabupaten Sleman - Virga Dwi Efendi; Yossyafaat, Herkin (Direktorat Pengabdian kepada Masyarakat, 2023)
The number of illegal poachers is increasing in the forest area of Kepuharjo Village, Kapanewon Cangkringan, Sleman Regency. This illegal hunting activity can disrupt the ecosystem and threaten the extinction of certain animal species. One of the iconic animals of Sleman Regency which is now starting to become rare is the punglor bird (red anis) which is often hunted by members of the public. Referring to the many reports from the public to the Kepuharjo district government, it shows that the massive number of animal poaching requires follow-up efforts to overcome this problem. This research aims to increase public understanding regarding the urgency of protecting animals by prohibiting animal hunting in the forest area of Kepuharjo Village. This research is a normative-empirical research that uses descriptive-qualitative analysis techniques and is strengthened by a case study approach. The results of the research show that the cause of the high number of illegal poaching in the Kepuharjo sub-district is due to a lack of public legal awareness and a lack of firmness in law enforcement relating to the prohibition of animal hunting. As an effort to reduce the number of illegal poaching that occurs in Kepuharjo Subdistrict, The Student Community Services-Community Empowerment Learning (KKN-PPM UGM) team collaborates with the Kepuharjo Subdistrict Government to establish animal protection efforts in the form of drafting Kepuharjo subdistrict regulations regarding animal protection, making signs. animal hunting ban installed in eight hamlet points, planning of a task force to eradicate illegal poaching and other steps implemented in the context of animal protection.